ANALISIS LIFE CYCLE COST (LCC) TERHADAP KEPUTUSAN RENOVASI ATAU PEMBONGKARAN (STUDI KASUS: GEDUNG X) - Ryan Faza Prasetyo; Sahara Reissa Amanda (Universitas Trisakti, 2023)
Life Cycle Cost is a method for estimating the total cost of owning a facility which includes all costs associated with purchasing, owning and disposing of a building or building system. It has long been understood that evaluating construction costs only on initial costs is not enough. Thus, it is necessary to calculate maintenance costs during the life of the building. Consideration of the usage costs required throughout the life of the building must be considered. The purpose of this research is to obtain the total cost of life cycle life cycle cost (LCC) for periodic maintenance per 20 years in building construction. In this study, the building to be reviewed is Building X of one of the universities. The part that is calculated for the Life Cycle Cost is the wall elements of the building taking into account the renovation and demolition methods. Through the LCC calculation process for wall work items in the two methods, a total demolition cost of IDR 2,249,506,566.56 was obtained and a total renovation cost of IDR 2,945,332,567. The cost of renovation is greater than the cost of demolition because the planned life of the building decreases during the renovation stage, so that the building must be demolished and costs more.